Next Generation Sequencing and Genetic Alterations in Squamous Cell Lung Carcinoma: Where Are We Today? - Friedlaender, Alex; Banna, Giuseppe; Malapelle, Umberto; Pisapia, Pasquale; Addeo, Alfredo (Frontiers in Oncology, 2019)
Lung cancer is the leading cause of cancer-related mortality and will affect approximately 6% of the population. It is divided into two broad categories, small cell lung cancer and non-small cell lung cancer, the latter representing 85% of all lung cancers. It mainly comprises adenocarcinoma (65%) and squamous cell carcinoma (30%) histologies. In recent years, there have been two major therapeutic advances in non-small cell lung cancer. The first, immunotherapy, has greatly improved the prognosis of adenocarcinomas and squamous cell carcinomas. The second, the treatment of targetable driver mutations, has so far only benefited adenocarcinomas. Squamous cell carcinoma carries a high rate of mutations and is found mostly among smokers. This raises two important problems: identifying driver mutations and finding those of clinical relevance. Large-scale genomic analyses such as The Cancer Genome Atlas have allowed for the identification of frequent gene alterations, although their role and potential for targeted therapy remain unknown. The emergence of next generation sequencing has changed the landscape of precision medicine, in particular in lung cancer. In this review, we discuss the landscape of genetic alterations found in squamous cell lung cancer, the results of current targeted therapy trials, the difficulties in identifying and treating these alterations and how to integrate modern tools in clinical practice.